ADVANCED AND NON- INVASIVE TECHNOLOGIES FOR IMAGING AND VISUALIZATION OF OBSTRUCTIVE LESIONS OF THE TRACHEOBRONCHIAL TREE- VIRTUAL BRONCHOSCOPY - Nikolova, Sonja (My University, 2018)
Virtual bronchoscopy is a new and non- invasive CT imaging technique that enables accurate intraluminal evaluation and depiction of the tracheobronchial tree. These novel and noninvasive techniques are important in future planning of interventional procedures, determining the therapeutical response and patient follow up. Aim: The main aim of this study will be to assess the diagnostic benefit of multi detector computed tomography (MDCT) post processing tools, such as virtual bronchoscopy (VB), multi planar reformatted (MPR) and minimum intensity projection (MinIP) images in the depiction of central airway stenosis. Study design: This will be a prospective study with a retrospective overview, that involves a total of 100 patients with airway disease symptoms in a period of two years. Materials and methods: 100 patients (60 men and 40 women), aged 20- 65 will be selected based on the presence of central airway lesions, detected previously during a routine axial CT scans, or prior fiber optic bronchoscopy and then a comparison will be made between axial scans, virtual bronchoscopy (VB), multi planar reformatted (MPR) and minimum intensity projection (MinIP) images, considering the fiber optic bronchoscopy as a gold standard. The central points of evaluating lesions will be the degree of luminal narrowing, the distance from carina, the length of the narrowed segment and the distal visualization of airways.
Keywords: airway; MDCT; tracheobronchial narrowing; virtual bronchoscopy